Tuberculose: uma doença negligenciada - Machado, Janete Aparecida; Adam, Mariana S.; Carneiro, Marcelo; Scheibler, Aline; Haas, Camila; Possuelo, Lia Gonçalves; Stahlecker, Eloete B. (Revista de Epidemiologia e Controle de Infecção, 2011)
.